Evaluation of several commercial synthetic polymers as flocculant aids for removal of highly concentrated C.I. Acid Black 210 dye - Abu Zahrim Yasser; C.Tizaoui; N.Hilal (Elsevier, 2010)
The removal of C.I. Acid Black 210 dye from highly concentrated solutions was studied using a coagulation/flocculation process. Aluminium sulphate was used as a primary coagulant and five commercial polymers were used as flocculant aids. The five commercial polymers were ACCEPTA 2058 (poly-diallyl-dimethyl ammonium chloride), ACCEPTA 2047 (high molecular mass (MM) anionic polyacrylamide), ACCEPTA 2111 (high MM cationic polyacrylamide), ACCEPTA 2105 (Low-medium MM cationic polyacrylamide) and ACCEPTA 2037 (Composite of high MM cationic polyacrylamide-inorganic salt(s)). The five polymers behaved differently and they showed maximum colour removal increment in the order: ACCEPTA 2058 > ACCEPTA 2037 > ACCEPTA 2111 ≈ ACCEPTA 2047 > ACCEPTA 2105. Results also showed that the aluminium sulphate is important as primary coagulant and settling time has significant effect on the dye removal.